"It gives you a better chance of getting a good job": memorable messages, anticipatory socialization, and first-year college students' understandings of the purpose of college. Issue 1 (2nd January 2022) - Ashby-King, Drew T.; Anderson, Lindsey B.
ABSTRACT: Higher education has been commodified as neoliberal ideology is reflected in and perpetuated through social discourses, such as memorable messages. These discourses socialize young adults to college and shape their understanding about the purpose of higher education. Through in-depth interviews with 20 first-year college students, we found that the memorable messages students received from their family, peers, and high school teachers reinforce the dominant neoliberal, job-centered understanding of college's purpose. In turn, we suggest critical communication pedagogy as a form of resistance instructors and institutions can use to promote a more expansive view of higher education and teaching/learning.